Doubly chloro bridged dimeric copper(ii) complex: magneto-structural correlation and anticancer activity1. Issue 19 (21st May 2015) - Sikdar, Yeasin; Modak, Ritwik; Bose, Dipayan; Banerjee, Saswati; Bieńko, Dariusz; Zierkiewicz, Wiktor; Bieńko, Alina; Das Saha, Krishna; Goswami, Sanchita
<x xml:space="preserve">Abstract</x> A doubly chloro bridged dinuclear copper(ii) complex was synthesized and magneto-structural correlation was drawn.The complex exhibits promising anticancer activity in HepG2 cells.